2019
DOI: 10.31234/osf.io/ub4p5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task Duration and Task Order do not Matter: No Effect on Self-Control Performance

Abstract: 24The strength model of self-control proposes that all acts of self-control are energized by one 25 global limited resource that becomes temporarily depleted by a primary self-control task, 26 leading to impaired self-control performance in secondary self-control tasks. However, failed 27 replications have cast doubt on the existence of this so-called ego depletion effect. Here, we 28 investigated between-task (i.e. variation in self-control tasks) and within-task variation (i.e. 29 task duration) as possible … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Furthermore, these durations of the Stroop task were utilized as previous research has employed this task for the same length of time (i.e., 4 min; Boat and Taylor, 2017 ). Also, 8 and 16 min reflect a 200 and 400% increase in duration, respectively, thus reflecting a suitable variance for differences to be observed and is in line with previous research (e.g., Wolff et al, 2019 ).…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, these durations of the Stroop task were utilized as previous research has employed this task for the same length of time (i.e., 4 min; Boat and Taylor, 2017 ). Also, 8 and 16 min reflect a 200 and 400% increase in duration, respectively, thus reflecting a suitable variance for differences to be observed and is in line with previous research (e.g., Wolff et al, 2019 ).…”
Section: Methodssupporting
confidence: 88%
“…Participants persisted at the wall-sit task 32 s longer on average, when they exerted self-control for a short duration (i.e., 4 min) relative to when they exerted self-control for a long duration (i.e., 16 min); equivalent to a 28% improvement in performance. This is interesting given that recent research has suggested that the initial task duration is not associated with the magnitude of performance impairment for physical ( Giboin and Wolff, 2019 ) or cognitive ( Wolff et al, 2019 ) performance. However, it is important to highlight that prior cognitive exertion appears to have a greater negative influence on performance during subsequent isolation tasks (e.g., wall-sit task), compared to whole-body endurance tasks (e.g., cycling) ( Giboin and Wolff, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Subhash and Sujoy’s narratives are good examples that show how abstinence from active sex life could make the LGBT adults more anxious during the lockdown. While Sujoy’s example reflects the high demand of self-control during the Covid-19 lockdown [ 48 ], research suggests that the application of self-control is effortful and aversive [ 49 ]. Therefore, individuals with low self-control could be at a higher risk of succumbing to their behavioral impulses during the pandemic.…”
Section: Discussionmentioning
confidence: 99%